Rola ubezpieczeń kredytów hipotecznych we wspieraniu rynku finansowania nieruchomości - Bulik, Magdalena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In the last few years there has been a rapid development on the mortgage market in Poland. The amount of the mortgage still increases. The property demand is evident The mortgage insurance appears to have a major role in the financial support on the property market in Poland. First of all, the mortgage insurance may increase the property availability for the potential home buyers. It also means the growth of the granted mortgage volume.. Moreover the mortgage insurance may take an important role in the private mortgage market development It increases the investors trustworthy by the mortgage support.The growth of the granted mortgage volume is the property market derive. Both, in Poland and foreign countries, the property market dynamically rises. The polish market increase forces the financial system development The insurance companies become to play a major role on the financial support on the property market If there is no a mortgage insurance system development and there is no financial source availability - there can not be the property financial market development The mortgage insurance means not only the insurance companies benefits, it also brings the profits to the banks and the clients. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 90-97